Development of Sharing Economy Business Model for Company Sustainability: A Case Study on Gojek - Lily Elvina Dewi; Didi Sundiman (Bina Nusantara University, 2023)
The definition of the sharing economy is still unclear and causes inconsistent research contributions and the application of the concept of the sharing economy business model. The research focused on developing sharing economy business model that supported sharing economy for company sustainability. The research approach was a qualitative research, the Â object was data related to the sharing economy business model on company sustainability. The sample data were collected from consumersâ€™ comments and reviews on the Gojek application on Google Playstore. The data used were 23.888 reviews. Then, Bigram was used as text processing and language developed by the system to identify topics in the comment data using Latent Dirichlet Allocation (LDA) topic modeling to determine trending topics. The results show that the sharing economy business model have an important role in company sustainability. There are important elements, such as type of platform, shared practice, place of interaction, review system, and revenue stream. The research also provides additional contributions to scientific development in the managerial field. It is expected to support the sharing economy theory and business model. Last, the research results can support and prove that the sustainable company is good at implementing the sharing economy business model for company sustainability.